Inuit and Polar Bears: Cultural Observations from a Hunt near Resolute Bay, N.W.T. - Wenzel, George (ARCTIC, 1983)
The relationship between Inuit and polar bear (Ursus maritimus Phipps) is examined. The emphasis is placed on cultural aspects of Inuit polar bear hunting. A single hunt near Resolute Bay, N.W.T., is described and comparisons are made to Inuit polar bear hunting behaviour in the Clyde River area of Baffin Island.Key words: hunting, Inuit culture, polar bear, Resolute Bay Mots clés: chasse, culture Inuit, ours blanc, Resolute Bay